Multi-modality ontologyfor herbal medicinal plant semantic based image retrieval - Sulaiman, Mohd Suffian; Nordin, Sharifalillah; Jamil, Nursuriati; Abdul Halin, Alfian (2014)
The demand of herbal medicinal plant as alternative treatment from nature becomes higher every year. Thus, a comprehensive knowledge repository is needed for user to access the right herbal medicinal plant information for their optimum health benefit. Unfortunately, current development of herbal medicinal plant repository only emphasize on the textual information. Therefore, it led to difficulty of user to obtain adequate knowledge especially the image of herbal medicinal plant. This paper presents a multi-modal ontology model that integrates textual and visual information of herbal medicinal plants. This model was designed base on the human perception of images where retrieval is performed at semantic level.